Answers

2014-07-02T00:59:33+05:30
Let acceleration be a m/s^2 and initial velocity be u m/s.
Now s(distance) in first part is 5 m and final velocity is 6m/s
therefore, using- v^2-u^2=2as we get,
6^2-u^2=2*a*5
=> 36-u^2=10a   --------- eq.1
now in second part of journey...6m/s becomes initial velocity, 8m/s becomes final velocity and 7m is s
again applying the same equation...we get,
8^2 - 6^2=2*a*7
=> 64-36=14a
=>28=14a
=>a=2m/s^2
NOW SUBSTITUTING VALUE OF a IN EQ. 1, WE GET-
36-u^2=10*2
=>36-u^2=20
=>36-20=u^2
=>16=u^2
=>u=4m/s
Therefore, we get- acceleration = 2m/s^2 and initial velocity= 4m/s

0